PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PENDEKATAN CONTEXTUAL, TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI SISWA KELAS IV SDK SANTO YOSEPH II NAIKOTEN KUPANG - Yanuaria Leki; Roswita Lioba Nahak; Kristina E. Noya Nahak (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Yanuaria Leki. (2026) Title: Development of Student Worksheets (LKPD) Based on the Contextual Teaching and Learning (CTL) Approach to Improve Poetry Writing Skills of Fourth Grade Students at SDK Santo Yoseph II Naikoten Kupang. Thesis. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University, Kupang. Supervisor I: Roswita L. Nahak, S.Pd., M.Pd., Supervisor II: Kristina E. Noya Nahak, S.Pd., M.Pd. This research is motivated by the low level of students' poetry writing skills due to the lack of use of innovative and contextual teaching materials in the learning process. Learning to write poetry is still dominated by conventional methods, resulting in students experiencing difficulties in finding ideas, determining themes, choosing diction, and developing poetry based on real experiences. Therefore, it is necessary to develop Student Worksheets (LKPD) based on the Contextual Teaching and Learning (CTL) approach that can help students connect learning materials with everyday life, thereby improving poetry writing skills. This research aims to develop a Contextual Teaching and Learning (CTL) approach to poetry writing for fourth-grade students at Santo Yoseph II Elementary School, Naikoten, Kupang. This research employed a Research and Development (R&D) method with the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques included validation questionnaires from linguists, material experts, and media experts, learning observation sheets, student response questionnaires, and poetry writing skill assessments. The results of the study indicate that the developed LKPD meets the criteria of validity, practicality, and effectiveness. The validation results obtained a percentage of 88% from language experts, a CVR value of 1.00 from material experts, and 89% from media experts, which is included in the very valid category. In addition to meeting the validity aspect, LKPD also meets the practicality aspect, as indicated by the results of learning observations of 78%, the results of teacher response questionnaires of 92%, and the results of student response questionnaires of 72%. These results indicate that LKPD is easy to use, receives very good responses from teachers and students, and is suitable for application in learning poetry writing in grade IV elementary school. Based on these results, it can be concluded that LKPD based on the Contextual Teaching and Learning (CTL) approach is suitable for use as teaching material in Indonesian language learning material on poetry writing for grade IV students of SDK Santo Yoseph II Naikoten Kupang.